Measurement of salivary Immunoglobulin A of participants with a healthy, gingivitis and chronic periodontitis conditions - Suzan A Salman (College of Dentistry/ University of Baghdad, 2015)
Background: Secretory Immunoglobulin A (SIgA) is a subclass of Immunoglobulin A (IgA), It is an antibody that plays an important role in mucosal immunity. It is the main immunoglobulin found in mucous secretions from mammary glands, tear glands and salivary glands, every pathologic process in the body involves the immune system, and periodontal inflammation is one of them and is not an exception. Material and methods: this study was consisted of 60 healthy male participants of an age ranged between (35-50) years old ; 25 of them with generalized moderate chronic periodontists(Clinical Attachment Loss equal to 3-4mm at ≥ 30% of the sites; 20 participants with plaque induced gingivitis and 15 participants had clinically healthy periodontium as control group. oral examination include Plaque Index, Gingival Index, Probing Pocket Depth and Clinical Attachment Level were conducted for all participants four sites were examined for each tooth (labial ,lingual, mesial and distal), 2ml of unstimulated whole saliva was collected from all participants to measure Secretory Immunoglobulin A in µg /ml by Enzyme-linked immunosorbent assay technique. Results: salivary IgA(sIgA) mean was (356.3) µg /ml for the chronic periodontitis patients; while it was 202 µg /ml for plaque induced gingivitis patients and it was 129.2 µg /ml for the control group. Highly significant differences among the three group were recorded (P-value